Pengaruh Dividend Payout Ratio (Dpr) Dan Return On Asset (Roa) Terhadap Harga Saham Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (Bei) - Situmorang , Mutiara; saribu, Ardin Dolok; Siahaan, Audrey M. (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The aim of this research is to determine the effect of the Dividend Payout Ratio (DPR) on share prices. To determine the effect of Return On Assets (ROA) on share prices. This research uses secondary data in the form of company financial reports. Sampling used purposive sampling. Data analysis uses the classic assumption test. Multiple linear regression test. The population in this study are food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange for the 2021-2023 period with a total sample of 21 companies. Data processing in this research uses the SPSS (Statistical Package for the Social Science) 26 software program. Based on research conducted on 21 Manufacturing Companies in the Food and Beverage Subsector on the Indonesia Stock Exchange in 2021-2023. So it can be concluded that the Dividend Payout Ratio (X1) has no significant effect on share prices with a calculated t value of 0.522 and a significant value of 0.546 0.05. The results of testing the second hypothesis show that Return On Assets (X2) has a significant effect on Share Prices (Y) with a calculated t value of 0.374 and a significant value of 0.021<0.05